Menggali Passion Membangun Karir: Pengabdian Masyarakat untuk siswa SMK - Nuristya, Emma Rani (STAIN SULTAN ABDURRAHMAN KEPRI, 2025)
This community service aims to help Vocational High School (SMK) students understand the importance of passion in choosing the right career. With the theme